What is language and why does this matter to English teachers? - Arias, Juan José (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2023)
In this reflective article, we critically analyse two definitions of language (i.e., language as a tool for communication and as a cultural artefact) along with arguments associated with them used to legitimise the teaching of English as a foreign language. We focus on some of the problems these definitions pose both from an educational and a linguistic/scientific perspective. After defining language as a biological capacity all human beings share, we explain what the relevance of this conception of language is in ELT.